Réponses

Meilleure réponse !
2014-03-23T22:43:29+01:00
Bonsoir,

Exercice 36

Il s'agit d'une application de la formule : a² - b² = (a + b)(a - b)

a) x² - 16 = x² - 4²
              = (x + 4)(x - 4)

b) 121 - x² = 11² - x²
                = (11 + x)(11 - x)

c) 1 - x² = 1² - x²
            = (1 + x)(1 - x)

d) x² - 144 = x² - 12²
               = (x + 12)(x - 12)
2014-03-23T22:58:23+01:00
a) x² - 16 = x² - 4² = (x + 4) (x - 4)

b) 121 - x² = 11² - x² = (11 + x) (11 - x)

c) 1 - x² = 1² - x² = (1 + x) (1 - x)

d) x² - 144 = x² - 12² = (x + 12) (x - 12)